Coexistence and Habitat Preference of Two Honeyeaters and a Sunbird on Lombok, Indonesia - Carstensen, Daniel W.; Sweeny, Redmond; Ehlers, Bodil; Olesen, Jens M. (Biotropica, 2011)
On the island of Lombok, Indonesia, three nectarivorous birds partially coexist: the two closely related and very similar Lichmera honeyeaters and a sunbird (Cinnyris jugularis). We investigated how these species segregated ecologically in areas where they coexisted by evaluating foraging visits and aggressive interactions at rich and poor nectar resources in different habitats (forest and open areas) along an altitudinal gradient (800-1600 m asl). The two honeyeaters were partially segregated by altitude. In the zone of overlap, Lichmera limbata dominated the richest forest resources, while Lichmera lombokia dominated the richest resources in open land. The sunbird, C. jugularis, was only observed in open habitats and mostly at poor resource patches. In the three-species community in open habitats a dominance hierarchy was apparent with L. lombokia as the superior species and C. jugularis as the inferior species. Studies on how segregated species interact in their transition zone can help us to understand interactions between otherwise ecologically segregated species.